Family Mediation: A Manifestation of Changes in Caring for Seniors - Rynkowska , Dorota (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
Our society is aging and the attitudes of children toward caring for their elderly parents are becoming an increasingly frequent cause of family conflicts, especially between siblings. Potential family conflicts, increasingly often concern decisions on the type, extent, and time of caring for aging parents. Sharing responsibilities and organizing care for the parents is a cause of growing tension inside families. Problems include the lack of clarity about the division of duties related to helping with general household chores (cleaning, preparing meals, shopping) between siblings or duties related to personal and general care (feeding, bathing, administering medications, making medical appointments, and recreation). The main research problem in this article is to define the caring function of the family and family relations in the context of caring for parents with the use of mediation. The research method used in the text was content analysis. Mediation is an increasingly popular procedure implemented to restore normal relations between conflicting parties, including family members. Apart from conciliation, arbitration, and negotiations, it is the most dynamically developing method of dispute resolution and an alternative to the existing procedures offered by the justice system. Family mediation can help families in making many difficult decisions. The advantages of this procedure result both from the fact that it offers a holistic approach to very complex problems that require an effective resolution, as well as from the involvement of a neutral third party facilitating and organizing the process of communication between family members.